Are three‐day voiding diaries feasible and reliable? Results from the Symptoms of Lower Urinary Tract Dysfunction Research Network (LURN) cohort. Issue 8 (25th July 2019) - Cameron, Anne P.; Wiseman, Jonathan B.; Smith, Abigail R.; Merion, Robert M.; Gillespie, Brenda W.; Bradley, Catherine S.; Amundsen, Cindy L.; Yang, Claire C.; Lai, Henry H.; DeLancey, John O.L.; Helmuth, Margaret E.; Bradley, Megan S.; et al.
Abstract: Aims: The aims of this study were to assess the completeness of voiding diaries in a research context and to correlate diary data with patient‐reported questionnaires. Methods: Men and women enrolled in the Symptoms of Lower Urinary Tract Dysfunction Research Network (LURN) were given a 3‐day voiding and fluid‐intake diary to fill‐out. Diaries were assessed for completeness and intake‐output imbalances. They were assigned to one of four categories based on a percentage of missing data and fluid imbalance: no diary submitted, unusable (>40% missing void or intake volumes, or unphysiological fluid imbalance), usable but not complete, and complete. Results: A total of 1064 participants were enrolled and 85% (n = 902) returned the bladder diary. Of the diaries returned, 94% (n = 845) had data on three separate days, 87% (n = 786) had no missing intake volumes, 61% (n = 547) had no missing voided volumes, and 70% (n = 635) had a fluid imbalance within 3 L across the 3‐day time period, resulting in 50% (n = 448) of participants with 100% complete diaries. Younger age was associated with a higher likelihood of not submitting a diary, or submitting an unusable diary. Women had a higher likelihood of submitting an unusable diary or a usable but incomplete diary. Conclusion: Overall, 50% of LURN participants returned voiding diaries with perfectly complete data. Incomplete data for voided volumes was the most common deficiency. There was only a moderate correlation between diary data and questionnaire responses, indicating that diaries are a source of unique information.